ANALISIS FENOMENA CHILDFREE TERHADAP TUJUAN PERKAWINAN PERSPEKTIF HUKUM KELUARGA ISLAM - Al Habibah Dina Nur Wahidah (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2026)
Marriage in Islam is a sacred institution aimed at establishing a harmonious family (sakinah, mawaddah, and rahmah) and preserving lineage as part of the maqashid al-shari’ah. However, in modern society, the childfree phenomenon—defined as the decision of married couples to not have children—has increasingly emerged.This study aims to analyze the childfree phenomenon and its implications for the objectives of marriage from the perspective of Islamic Family Law. This research employs a qualitative descriptive method with empirical and philosophical approaches, utilizing both primary and secondary data sources analyzed through content analysis techniques.The findings indicate that within Indonesian society, the presence of children is still considered an essential component of family life and a symbol of happiness. In Islamic perspective, having offspring is one of the primary objectives of marriage, closely related to the protection of lineage (hifz al-nasl). Therefore, normatively, the childfree choice is considered inconsistent with the fundamental purpose of marriage.Nevertheless, in certain circumstances that involve greater benefit (maslahah), such as physical, mental, or economic incapacity, or potential harm, Islam provides limited flexibility for such a decision. Thus, the childfree phenomenon should be understood comprehensively by considering normative, social, and individual aspects, while remaining aligned with the principle of maslahah in Islamic Family Law.